Putting ITIL® Into Practice: Applying ITIL® 3 Foundation Concepts. - Pultorak, David (linkedin.com, 2018)
Learn how to put the seven key ITIL® Foundation concepts into practice. This course shows how to apply concepts such as the service management lifecycle to real-world IT scenarios.